Tecnologia educacional para capacitação em ilustração botânica, Amapá, Brasil - NEGRÃO, Mariellen Furtado (Instituto Federal do Amapá, 2021)
Educational technology is needed in education planning. The appeal that the technological revolution brings to daily life requires that planning be constructed in order to encompass, in addition to the theoretical content, technological tools to aid the development of more meaningful learning. As the main characteristic of this flexibility in space-time, in an educational model that uses the technology to aid the activities of classroom. These tools enable the student to create other environments to establish and enhance individual development. Thus, learning happens without necessarily being linked to the physical space pre-established in the school environment or in the classroom. Thus the objective of the present work is: to verify how educational technology can assist in the training in botanical illustration. The method used to organize the course was based on the purposes of a university extension course for the development of extension courses, according to the following steps: (1) lecture, (2) selection of academics, (3) (4) introduction to the content taught, (5) establishment of a program of complementary activities, (6) illustrated morphological study of the list of plant species, and (7) completion of the course. The course enabled the transfer of techniques of scientific illustration to which academics; the students presented a satisfactory evolution, and this relationship was perceived with the quality of the illustrations made by the participants of the course, and the use of educational tools was one of the vehicles that helped to develop their ability.